Prestationsmätning i förhållande till lean ledarskap : En fallstudie på SSAB som genomgår en lean transformation - Pendse, Oscar (2016)
Lean Management is currently one of the foremost management initiatives embraced by several industries in striving to obtain high quality and sustainable competitive advantages to the lowest costs. A Lean leadership is described by researchers as a framework for ideal value creation, and a prerequisite to succeed with a Lean transformation. Sustaining Lean leadership put emphasis on the importance that the Performance Measurement (PM) of leaders are aligned and adjusted with the fundamentals of Lean leadership principles. This is stated to be important in order to capture the full potential of leaders and to exclude any possible drawbacks of a PM system that is contrary to the leadership approach. As for today, limited studies have been conducted addressing the area of how to assess leadership performance while undertaking a Lean transformation, specifically in the process industry. The purpose of this study was to identify how the Swedish steel actor Swedish Steel AB (SSAB) could assess leadership performance, so the PM related to leadership was aligned with the management philosophy applied at SSAB.This study was performed as a descriptive and exploratory case study and adopted an inductive approach. Qualitative data was analysed through content analysis and data display. A literature review was conducted, and empirical data was gathered from a number of sources but primarily from the division of SSAB ONE, since it has the responsibility to start facilitating the Lean transformation at SSAB. High performance leaders and the head of human resources at SSAB Luleå were also interviewed to get a holistic view of the context at SSAB.In consensus with the division of SSAB ONE, 15 important characteristics of Lean leadership to support the Lean transformation at SSAB were identified as: curious, open-minded, altruistic, prestigeless, holistic thinking, self-aware, positive, patient, passionate, emphatic, courageous, visionary, honest, humble, and a being a good listener. Using these characteristics and its described ...